1990
DOI: 10.1176/ajp.147.10.1297
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive effects of corticosteroids

Abstract: In three independent studies with different designs and groups of subjects, the authors found that 1) depressed patients who did not suppress cortisol when given dexamethasone (compared to suppressors and normal control subjects), 2) healthy volunteers given a single 1-mg dose of dexamethasone (compared to those given placebo), and 3) healthy volunteers given 80 mg/day of prednisone for 5 days (compared to those given placebo) all made significantly more errors of commission in verbal memory tasks, with no sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 367 publications
(29 citation statements)
references
References 44 publications
2
26
0
1
Order By: Relevance
“…In addition, although administering hydrocortisone for four days successfully increased circulating cortisol to high physiological levels (Schoorlemmer, et al, 2009) and produced similar cognitive impairments to those reported with in other studies of exogenous or endogenous manipulation of cortisol levels (Wolkowitz, et al, 1990), endogenous alterations of cortisol accompanying increased stress are associated with other hormonal changes (e.g., ACTH) that may have independent effects on the central nervous system (McEwen, 2008). One goal of this study was to model the Shors et al animal work that examined the interactive effects of estradiol and acute stress.…”
Section: Discussionsupporting
confidence: 60%
“…In addition, although administering hydrocortisone for four days successfully increased circulating cortisol to high physiological levels (Schoorlemmer, et al, 2009) and produced similar cognitive impairments to those reported with in other studies of exogenous or endogenous manipulation of cortisol levels (Wolkowitz, et al, 1990), endogenous alterations of cortisol accompanying increased stress are associated with other hormonal changes (e.g., ACTH) that may have independent effects on the central nervous system (McEwen, 2008). One goal of this study was to model the Shors et al animal work that examined the interactive effects of estradiol and acute stress.…”
Section: Discussionsupporting
confidence: 60%
“…Smaller hippocampi have been found in adults who have experienced early adversity (Wolkowitz et al, 1990; Newcomer et al, 1994; Keenan et al, 1996; Bremner et al, 1997; Perry, 2001; Heim et al, 2002; Lupien et al, 2005; Teicher et al, 2006), but not in children (Carrion et al, 2001; De Bellis, 2001; De Bellis et al, 2002; Woon and Hedges, 2008), nor in adolescents (Carrion et al, 2001; De Bellis, 2001; De Bellis et al, 2002; Woon and Hedges, 2008; Frodl et al, 2010; Rao et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Excessive circulatory levels of corticosteroids were observed to be associated with cognitive impairment in various disease states (34). Wolkowitz et al (35) found that even a single dose (1 mg dose of dexamethasone) or short-term use of corticosteroids (80 mg dose of prednisone for 5 days) was significantly related to memory problems and raised the possible adverse effect of corticosteroids on cognitive function. This result implies that even patients with relatively low-dose glucocorticoid use may be at risk for cognitive problems.…”
Section: Discussionmentioning
confidence: 99%